Characterizations of Cu-based coated Al7075 via plasma-spray method - A wear case study - Ghazali M.J.; Mat Kamal S.E.; Abdullah S.; Misran H. (2023)
Despite of its poor tribological properties (low hardness and low resistance to friction, wear and abrasion as well as poor seizure resistance), aluminum has become a potential material in automotives, particularly in the engine areas. To overcome these weaknesses and increase the engine lifetime, a good surface treatment can be one of the best options. In this work, Cu-Ni alloy that has such excellent properties like ductility, corrosion and wear resistance, good electrical and thermal conductivity as well as it can be easily joined or fabricated into useful shapes, was chosen. The work aims to study the wear behavior of Cu-Ni coatings deposited on Al7075 substrates using an atmospheric plasma spray (APS) with different level of plasma powers. Lubricated wear test were carried out on a pin-on-disc tester under an applied load of 100 N with a fixed sliding speed of 0.851 ms-1 at room temperature (? 23C). It was found that a decrease in plasma power from 40 kW to 30 kW promoted finer microstructures and higher hardness of the coatings, up to 39%. At 30 kW, the splats formation involved high degree of flattening and solidification without many splashes within the structure. At higher power (40 kW), both velocity and temperature of droplets were noted to be increased, resulting rougher coating structures which were most likely due to overlapped splats. In turn, this weakened the bonding strength between splats. In the case of wear, the resistance of Cu-Ni coated Al7075 was found to be increased from ?6 to 18 10-5 mm3/Nm, indicating a mild wear regime that was attributed to an increase in the coating hardness. 2011 World Scientific Publishing Company.